Life in the Treetops: Ecophysiological Strategies of Canopy Epiphytes in a Tropical Montane Cloud Forest - Gotsch, S. G.; Nadkarni, N.; Darby, A.; Glunk, A.; Dix, M.; Davidson, K.; Dawson, T. E.
Tropical montane cloud forests (TMCFs)inhabit regions rich in biodiversity that play an important role in the local and regional water cycle. Canopy plants such as epiphytes and hemiepiphytes are an important component of the biodiversity in the TMCF and therefore play a significant role in the carbon, nutrient, and water cycles. With only partial or no access to resources on the ground, canopy plants may be vulnerable to changes in climate that increase canopy temperatures and decrease atmospheric humidity or precipitation inputs. Despite their importance in the TMCF, little is known about variation in functional strategies relating to drought voidance or drought tolerance of canopy plants. In this study, we quantified variation in a number of functional traits in 11 species of epiphytes and hemiepiphytes in a Costa Rican TMCF. We also generated pressure-volume and xylem vulnerability curves that we used as indicators of drought tolerance. In addition, we handsectioned fresh leaves and examined cross sections under a microscope to quantify leaf thickness, mesophyll thickness and the thickness of water storage cell layers (i.e., hydrenchyma), if present. Lastly, we determined the capacity for foliar water uptake in the laboratory and measured whole-plant transpiration in the field. A trade-off was found between traits that confer relative drought resistance and foliar water uptake capacity vs. traits that confer leaf capacitance and relative drought avoidance. This trade-off may represent an additional axis of the leaf economics spectrum that is unique to epiphytes. We also found that all species had the capacity for foliar uptake of water and that this process contributed substantially to their water balance. On average, foliar uptake of water contributed to the reabsorption of 70 percent of the water transpired over a relatively wet, 34-day study period. Our results indicate that canopy plants can mitigate water loss substantially via internal water storage or that they can directly utilize cloud water to offset losses. Our results indicate that species that rely on foliar uptake of water may be more vulnerable to projected changes in climate than species that buffer the effects of drought via internal water storage.
Keywords: CAPACITANCE; DROUGHT TOLERANCE; FOLIAR WATER UPTAKE; FUNCTIONAL TRAITS; HEMIEPIPHYTES; PRESSURE-VOLUME CURVES; VULNERABILITY CURVES; WATER RELATIONS